Enhancing Students’ Recount Writing Skills through Digital Storytelling in an EFL Classroom - Raudatul Jannah; Hendrik J. Maruanaya; Wenda M. Kakerissa (ITScience (Information Technology and Science), 2026)
This study aimed to improve students’ recount writing skills by implementing digital storytelling in an English as a Foreign Language (EFL) classroom. The study employed Classroom Action Research (CAR), consisting of two cycles, each including planning, action, observation, and reflection stages. The participants were 29 tenth-grade students. Data were collected through writing tests, classroom observations, and student questionnaires. The results showed a significant improvement in students’ writing performance. In Cycle 1, most students were categorized at the “poor” and “fair” levels, with a mean score of 61.0. However, in Cycle 2, the mean score increased substantially to 84.1, and 75.9% of the students achieved the “good” level, meeting the predetermined criterion of success. Improvements were observed in all aspects of writing, including content, organization, vocabulary, language use, and mechanics. In addition, the findings revealed that students responded positively to the implementation of digital storytelling, demonstrating increased motivation, engagement, and participation. The integration of multimedia elements helped students generate ideas, organize events more coherently, and express their experiences more confidently. These findings suggest that digital storytelling is an effective instructional medium that provides meaningful input and supports the writing process,s rather than merely serving as a tool for digital product creation. Therefore, it is recommended that EFL teachers integrate digital storytelling into writing instruction, particularly to help students develop ideas and improve overall writing quality.